Penerapan Terapi Slow Stroke Back Massage (SSBM) pada Lansia dengan Hipertensi di Desa Gerdu Kabupaten Sragen - Lutfi Alvianika; Riyani Wulandari (Lembaga Pengembangan Kinerja Dosen, 2024)
Background; Hypertension in Central Java Province affects 8.700.512 (30,4%) with a prevalance of hypertension in Sragen is 250.035 people. Generally, hypertension is suffered by elderly people. As they age, the elderly develop hypertension due to physiological factors that cause loss of elasticity and stiffness in blood vessels. Uncontrolled hypertension can cause complications and affect the quality life for elderly. Non-pharmacological therapies such as massage to lowering blood pressure. One of the non-pharmacological therapies is Slow Stroke Back Massage (SSBM). Purpose; To describe the results observations of Slow Stroke Back Massage (SSBM) therapy as an effort to reduce blood pressure in elderly people with hypertension. Method; This method uses descriptive case study analysis and a sphygmomanometer to measure blood pressure. SSBM therapy is applied for 10 minutes, 3 times a week, over 4 weeks. Results; After applying SSBM therapy, there was a decrease in respondent I and II's within the category range of stage I hypertension. Conclusion; The application of SSBM therapy in elderly people with hypertension can reduce blood pressure.